Comparative Effect of Organic and In-Organic Fertilizer Treatment on the Growth and Tuberyeild of Sweet Potato (Ipomea Batata L) - A.S, Adeyeye; W.B, Akanbi; O.O, Sobola; W.A, Lamidi; K.K, Olalekan (International Journal of Sustainable Agricultural Research, 2017)
The experiment was conducted at the teaching and Research farm of the Federal University Wukari Taraba State, Nigeria to assess, evaluate and compare the effect of organic fertilizers such as poultry manure, cow dung, organic manure and in-organic fertilizers such as NPK and urea on the growth and tuber yield of sweet potato. The recommended rates of cow dung (10t/ha) poultry manure (10t/ha), organic manure (10t/ha) NPK15:15:15 (400kg/ha) and urea (200kgN/ha) were applied as treatment to sweet potato with a control at (0kg/ha). These were arranged in a randomized complete block design with three replications. Measurement were taken on the growth and tuber yield at harvest such as the length of primary vein, number of secondary vein number of leaves, number of tuber and tuber weight. Data collected were analyzed using (ANOVA) and the significant means separated using Duncan multiple difference at 5% probability level. The result revealed or showed that numbers of leaves were significant in all the treatments. Application of urea fertilizer produced the highest number of tuber per plant, while tuber weight was not significantly different, but poultry manure application had the higher mean value of (2.34kg). It was concluding that application of poultry manure as organic fertilizer are better and can compare readily with inorganic fertilizer (urea) in the production of sweet potato.